Which Improves Welfare More: Nominal Or Indexed Bond? - Martine Quinzii; Michael Magill (University of California, Department of Economics, 1995)
Despite economists'' long standing arguments in favor of systematic indexation of loan contracts to remove the risks associated with fluctuations in the purchasing power of money (Jevons (1875), Marshall (1887, 1923), F~lsher (1922), Friedman (1991)), surprisingly few loan contracts are indexed in most Western Eclonomies. fin the United States even thirty year corporate and government bonds are not indexed. The situation is however different in many Latin American countries where indexing is widely used as a way of coping with high and variable inflation rates. What seems difiicult to eicplain is that it takes lvgh variability in inflation rates before private sector agents shift from lmindexed to indexed contracts. In practice, indexing a loan contract m.eans linking its payoff to the value of an officially computed price index such as the Consumer Price Index (CPI). Such an index is always an imperfect measure of the purchasing power of money: in particular, it fluctuates not only with variations in the general level of prices but also varies with changes in the relative prices of goods. This paper formalizes the idea that the imperfections of indexing may serve tal explain why agents prefer nominal bonds in economies with a low variability in purchasing power of money and only resort to indexing when the variability becomes sufficiently high. The model is a variant of the two-period general equilibrium model with incomplete markets (GEI) in which the purchasing power of money depends on a (broadly defined) measure of the amount of money available in the economy and on an index of real output. The objective of the analysis is to compare two second-best situations, in which in addition to a given security structure, there is either a nominal bond which has the risks induced by fluctuations in the purchasing power of money or an indexed bond which has the risks induced by relative price fluctuations. Adding a bond to an existing market structure has two effects: the first is the direct effect of increasing the span of the fmancial markets i.e. increasing the opportunity sets of agents for transferring income; the second is the indirect effect of changing spot and security prices, which can either increase or decrease agents'' welfare. This paper only compares direct effects, all indirect effects being absent by virtue of the specification of agents'' preferences. The direct effects are always present, even with more general preferences, but some of the results that we
Keywords: 330